Analisis Komunikasi Interpersonal Guru dan Siswa dalam Mencegah Kasus Kekerasan Fisik dan Bulying (Study Kasus SMKN 1 Bolo) - Muhammad Muhammad (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
a case of violence in 2023 involving second grade students with third grade students at SMKN 1 Bolo. The incident involved the police because the teacher was unable to break up the fight because of the many people involved. This study aims to determine the role of interpersonal communication and students in preventing cases of physical violence and bullying. How effective is interpersonal communication. The method used in this study is qualitative, using data collection techniques, namely interviews, observation and documentation. The results of the study show that bullying is a case of violence that often occurs at SMKN 1 Bolo and is the cause of cases of violence such as fights and brawls between schools. interpersonal communication carried out by BK teachers and students has not been effective in preventing cases of violence. This is evidenced by cases of violence that occur every year.